Complementary Logic Circuits Based on High‐Performance n‐Type Organic Electrochemical Transistors. Issue 9 (10th January 2018) - Sun, Hengda; Vagin, Mikhail; Wang, Suhao; Crispin, Xavier; Forchheimer, Robert; Berggren, Magnus; Fabiano, Simone
Abstract: Organic electrochemical transistors (OECTs) have been the subject of intense research in recent years. To date, however, most of the reported OECTs rely entirely on p‐type (hole transport) operation, while electron transporting (n‐type) OECTs are rare. The combination of efficient and stable p‐type and n‐type OECTs would allow for the development of complementary circuits, dramatically advancing the sophistication of OECT‐based technologies. Poor stability in air and aqueous electrolyte media, low electron mobility, and/or a lack of electrochemical reversibility, of available high‐electron affinity conjugated polymers, has made the development of n‐type OECTs troublesome. Here, it is shown that ladder‐type polymers such as poly(benzimidazobenzophenanthroline) (BBL) can successfully work as stable and efficient n‐channel material for OECTs. These devices can be easily fabricated by means of facile spray‐coating techniques. BBL‐based OECTs show high transconductance (up to 9.7 mS) and excellent stability in ambient and aqueous media. It is demonstrated that BBL‐based n‐type OECTs can be successfully integrated with p‐type OECTs to form electrochemical complementary inverters. The latter show high gains and large worst‐case noise margin at a supply voltage below 0.6 V. Abstract : Ladder‐type polymers such as poly(benzimidazobenzophenanthroline) (BBL) can work as stable and efficient n‐channel materials for organic electrochemical transistors (OECTs). BBL‐based OECTs show high transconductance and excellent stability in ambience and aqueous media. These devices can be integrated with p‐type OECTs to form electrochemical complementary inverters, yielding high gains and large worst‐case noise margin at a supply voltage below 0.6 V.